Data Warehouse Implementation Techniques In Data Processing (Case Study Data Sales at PT Spirit Sejahtera Bersama): Data Warehouse Implementation Techniques In Data Processing (Case Study Data Sales at PT Spirit Sejahtera Bersama) - Made Hanindia Prami Swari; Fawwaz Ali Akbar; Martoni Martoni (Institute of Computer Science (IOCS), 2019)
Data Warehouse is a technique that can provide a facility for the storage and management of historical data from various internal and external sources so that it can be used in making strategic decisions for the company. A characteristic that distinguishes ordinary data warehouse database was largely on the data source that can not necessarily uniform and comes from one source as happened in PT Sejahtera Bersama spirit. The company is engaged in the sale of medical equipment, up to now has more than 70 showrooms and is divided in 12 regions, of which the sales information system used by the company in each region has a separate database in excel format, this is what makes firms difficulty in the process analyzing the sales data of the company. This research aims to design and build a data warehouse system to support marketing performance assessment and achievement of sales at PT Sejahtera Bersama spirit. Data modeling methods used in the design of data warehouse in this study is the dimensional modeling star schemas. Results from this study is a web-based dashboard application that will display sales data from the data warehouse is equipped with charts and reports, and the results of tests with the method of black box testing can be seen that the system has been going well as expected. Data modeling methods used in the design of data warehouse in this study is the dimensional modeling star schemas. Results from this study is a web-based dashboard application that will display sales data from the data warehouse is equipped with charts and reports, and the results of tests with the method of black box testing can be seen that the system has been going well as expected. Data modeling methods used in the design of data warehouse in this study is the dimensional modeling star schemas. Results from this study is a web-based dashboard application that will display sales data from the data warehouse is equipped with charts and reports, and the results of tests with the method of black box testing can be seen that the system has been going well as expected.